Teachers' Perspectives on Parenting Education in Rural Schools : A Case Study in the Indonesian Context - Supriadi, Yadi (My University, 2025)
This study investigated teachers' views of parenting education in Indonesian rural schools, based on the previous studies on effective parenting education that can help enhance academic performance. Parenting education is still not a formal requirement from the Indonesian government with the recent curriculum. Parenting education has its unique challenges in rural areas. Guided by Epstein’s Framework of Six Types of Involvement, this research addressed three central questions: (1) According to teachers, how do they perceive parents’ current capabilities in supporting their children’s learning at home? (2) What are the barriers that prevent rural parents from participating in school events and decision-making according to teachers? And (3) Based on teachers’ perspectives, how can the community and improved communication between parents and schools support the implementation of parenting education in rural schools? Six teachers at the kindergarten, elementary, and vocational high school levels were interviewed using a qualitative, multiple case study approach. Thematic analysis resulted in six main themes: communication, parental support at home, collaboration with the school community, decision-making, volunteerism, and parenting support structures. Overall, the study found that some parents show signs of care and motivation to help their children succeed in their learning process, but several barriers were found in the way of engaging support, including low levels of technological literacy, lack of time, and financial pressures. Teachers addressed that there should be improved communication systems, involvement in the local community, and structuring guidance to enhance the role of the parent in education for this particular rural area. This study illustrated the contextual complexities of the parenting education in the rural context. Moreover, it contributes to broader discourses on inclusive, empathetic, and community-based engagement in parenting education. Finally, it offers practical examples of how rural schools and educators adapt in their complex environments for the sake of promoting student growth and agency, and to provide support for the student family-and-community connection. Future study can work on parents’ perspectives on their role as a learner in parenting education.
Keywords: parenting education, rural schools, teachers’ perspectives, parental involvement, Epstein.